2011
DOI: 10.1097/cji.0b013e31822bc3d0
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Human Lymphocyte Cryopreservation

Abstract: In order to understand human inflammatory diseases and to develop and assess new therapeutic strategies targeting leukocyte recruitment to tissue, it is necessary to study human lymphocyte interactions with endothelium. It is often not practical to carry out assays on fresh human samples and therefore cells may be cryopreserved and batched for later study. Furthermore, many forms of adoptive cell therapy use cryopreserved cells that are required to migrate to tissue after infusion in vivo. The consequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
3
2
1
Order By: Relevance
“…2, P > 0.5, ANOVA) indicating functional integrity of PBMC after thawing. These data are consistent with previous findings that cryopreservation did not affect integrins on mononuclear cells (8,11).…”
Section: Accepted For Publication 20 February 2013supporting
confidence: 94%
See 1 more Smart Citation
“…2, P > 0.5, ANOVA) indicating functional integrity of PBMC after thawing. These data are consistent with previous findings that cryopreservation did not affect integrins on mononuclear cells (8,11).…”
Section: Accepted For Publication 20 February 2013supporting
confidence: 94%
“…2, P > 0.5, ANOVA) indicating functional integrity of PBMC after thawing. These data are consistent with previous findings that cryopreservation did not affect integrins on mononuclear cells (8,11).Overall, based on this limited set of markers, there was no indication for diminution or selection by cryopreservation of PBMC subpopulations, thus confirming and extending previous reports (2,4,12). In addition, our finding that cryopreservation of PBMC from several volunteers apparently did not affect their capacity to interact with activated endothelial cells now lends experimental evidence to the notion that cryopreservation is a useful tool to preserve native human immune cells for long-term or repeated functional analyses, at least regarding dynamic interactions with endothelial cells.…”
supporting
confidence: 82%
“…Cryopreservation of PBMC might also constitute a source of changes in labile phenotypic markers and B-cell subset distribution. Recently, Faint and coworkers showed that cryopreserved sample batching, and subsequent thawing for deferred analysis, did not alter the proportion of lymphocyte subsets but led to an increased CXCR4 expression on lymphocytes [52]. In our hands, the cryopreservation step indeed influenced positively CXCR4 expression on control B cells (Additional file 2: Figure S2).…”
Section: Discussionsupporting
confidence: 50%
“…Faint et al. investigated the effect of cryopreservation on lymphocyte migration and adhesion and demonstrated no functional effect but again noted an increased expression of CXCR4 [41] .…”
Section: Discussionmentioning
confidence: 99%